rbFOX1/MBNL1 competition for CCUG RNA repeats binding contributes to myotonic dystrophy type 1/type 2 differences - Chantal Sellier (Nature Portfolio, 2018)
Myotonic dystrophy (DM) type 2 is a neuromuscular pathology caused by large expansions of CCTG repeats. Here the authors find that rbFOX1 RNA binding protein binds to CCUG RNA repeats and competes with MBNL1 for the binding to CCUG repeats, releasing MBNL1 from sequestration in DM2 muscle cells.